A Strategy for Accelerated Seleccton and Release of Advanced-generation Eucalypt Species Hybrids - Venkatesh, C. S. (Indian Forester, 1982)
This paper outlines the strategy for concurrent multiplication testing, selective breading and utilization or the second and feather advanced generation hybrids of two promising interspecific crosses between Eucalyptus tereticonis Sm. and E. camaldulensis Dehnh. two of the most widely grown species of this genus in the world today. The advantage of using second generation hybrids in preference to those of the first, are explained. In order to ensure concurrent practical benefits, clonal plantations are envisaged after every step of selection.